Pumpkinheads - Rowell, Rainbow 1973- (Macmillan Children's Books, 2019)
"Deja and Josiah are seasonal best friends. Every autumn, all through high school, they've worked together at the world's best pumpkin patch. They say good-bye every Halloween, and they're reunited every September 1. But this Halloween is different. Josiah and Deja are finally seniors. It's their last season at the Patch, their last shift together--their last good-bye. Josie's ready to spend the whole night feeling melancholy about it. (He's the melancholy type.) But Deja has a plan: What if, instead of moping and instead of the usual--slinging lima beans down at the Succotash Hut--they went out with a bang? They could see all the sights! Taste all the snacks! Maybe Josie could even talk to that cute girl he's been mooning over for three years ... What if their last shift was an adventure?"--Provided by publisher